Pemberdayaan masyarakat Melalui Sosialisasi Senam Kegel Pada Lansia dan Pelatihan Kreativitas - Sonya Nelson (DEPARTEMEN KESEHATAN DAN REKREASI UNIVERSITAS NEGERI PADANG, 2025)
The area targeted by PKM is Nagari Bukik Batabuah, Canduang District, Agam Regency, which has a fairly large elderly population. As for partner problems: (1) The activities at the elderly posyandu are classified as monotonous so there is a lack of interest in participants coming, the posyandu activities are only reflected in the process of checking the health of the elderly, for example in weighing, checking blood pressure, sometimes also checking cholesterol and uric acid. There is still a lack of activities aimed at improving physical fitness and exercise for the elderly, which until now is rarely done. This is also due to the lack of instructors who are competent in providing counseling and training in order to create a physically and spiritually healthy society. Activities at the Posyandu are less varied and there is no special emphasis on carrying out exercise for elderly participants. Therefore, it is necessary to provide health education and training on exercise for the elderly. The target to be achieved is an understanding of 1) elderly exercise, especially sexual exercise (Kegel) as well as the proper and correct implementation of exercise. As for the second problem (2), regarding employment, especially for the elderly without potential, the majority of them are elderly who are no longer working even though they still want to work. Some elderly people are still less productive, which has the consequence of reduced income which can lead to elderly poverty. Therefore, it is necessary to provide creativity skills training based on local wisdom. The achievement target is to increase the productivity of the elderly, increase skills and have the opportunity to be developed into a business that is able to provide added value for families with not large capital but capable of generating quite high economic value.